(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Many studies were conducted in home and abroad on the subject but there is none in Chattogram region of Bangladesh. To unveil the existing situation we have conducted the study which will help better case management. Materials and methods: Properly diagnosed 54 consecutive type 2 diabetic patients with Acute Coronary Syndrome were selected for study. The study was conducted in 2016 (One year) at a private cardiac center of Chattogram city. After adequate preparation angiography was performed with standard Judkin’s technique. Data were manually managed and statistically analyzed. Results were compared with other similar studies. Informed consent was taken from the patients and the hospital authority before conducting the study. A competent institutional review board approved the protocol. Results: Sex of the patients were male 85% and female 15%. Age range was 30-70 years. Peak age group was 50-60 years. It was 41%. Mean age was 56±6.8 years. Multiple Vessels Disease (MVD) was the highest 39%. Commonly affected vessel was Left Anterior Descending artery (LAD) 83%. Conclusion: Diabetes mellitus is a notorious risk factor for coronary artery disease. It causes coronary artery lesions earlier. It significantly causes acute coronary syndrome. So all measures should be taken to prevent and control diabetes mellitus. Chatt Maa Shi Hosp Med Coll J; Vol.19 (2); July 2020; Page 21-22